Corporate ownership and control in Victorian Britain1. (10th November 2014) - Acheson, Graeme G.; Campbell, Gareth; Turner, John D.; Vanteeva, Nadia
<x xml:space="preserve">Abstract</x> Using ownership and control data for 890 firm‐years, this article examines the concentration of capital and voting rights in British companies in the second half of the nineteenth century. We find that both capital and voting rights were diffuse by modern‐day standards. However, this does not necessarily mean that there was a modern‐style separation of ownership from control in Victorian Britain. One major implication of our findings is that diffuse ownership was present in the UK much earlier than previously thought, and given that it occurred in an era with weak shareholder protection law, it somewhat undermines the influential law and finance hypothesis. We also find that diffuse ownership is correlated with large boards, a London head office, non‐linear voting rights, and shares traded on multiple markets.